EKSPERIMENTASI PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI SELF-EFFICACY SISWA - Yosi Pebriani; Ade Susanti (Pendidikan Matematika | STKIP YM Bangko, 2020)
The purpose of this study is to describe the mathematical communication skills that are taught with a scientific approach better than conventional learning of class IX students of SMP Negeri 43 Merangin 2019/2020 academic year. This research uses a quantitative approach with an experimental method. The sampling technique uses simple random sampling. Samples are grouped by self-efficacy high, medium and low. Data collection techniques using test and non-test. Analysis technique uses t-test and two-way ANOVA. The test results state that: mathematical communication skills both overall and with self-efficacy high, moderate and low taught with a scientific approach are better than conventional learning, and there is an interaction between scientific approaches and conventional learning in terms of self-efficacy in influencing mathematical communication skills.